Clinical characteristics of diffuse large B-cell lymphoma complicated with multiple primary malignant neoplasms - Tian, Mingxi; Gu, Xuejiao; Lv, Bin; Li, Yanhui; Huang, Ziqing; Li, Xinyi; Zhang, Yan; Wang, Ying; Zhu, Feng (Frontiers in Oncology, 2025)
ObjectiveTo investigate the clinical features and prognosis of diffuse large B-cell lymphoma (DLBCL) combined with multiple primary malignant neoplasms (MPMNs).MethodsThe clinical data and prognosis of 31 patients with DLBCL combined with MPMNs diagnosed by pathology between January 2012 and April 2024 in the Department of Hematology, Affiliated Hospital of Xuzhou Medical University were retrospectively analyzed.ResultsBetween January 2012 and April 2024, a total of 937 patients were diagnosed with DLBCL, among whom 31 patients had MPMN, with an incidence rate of 3.3%. The cases were divided into two groups according to the different occurrence intervals of the two tumor types. There were 10 patients in the synchronous MPMN group and 21 in the metachronous MPMN group. Statistically significant differences in gender (P=0.046), lactate dehydrogenase levels (P=0.040), and B symptoms (P=0.022) were noted between the two groups. The median age at first (Age 1) and second (Age 2) malignancy diagnoses was 62 (32–87) and 65 (38–87) years, respectively. The median interval between the two tumors was 15 (0–300) months. Kaplan-Meier survival analysis revealed that Age 1≥60 years, synchronous tumors, International Prognostic Index score of medium, high, and high-risk groups (3–5 points), interval time of two malignancies of <50 months, B symptoms, elevated LDH level, Eastern Collaborative Oncology Group score of ≥2 points, and radiotherapy and chemotherapy for the first tumor were adverse factors affecting overall survival.ConclusionsDLBCL combined with MPMNs is rare in the clinic. Age 1≥60 years and shorter time interval between the two tumors are the main factors affecting poor prognosis. Early diagnosis and treatment of DLBCL with MPMNs should be prioritized clinically to prevent misdiagnosis and enhance patient outcomes.